CURRENT RELEVANCE OF PANDIT MADAN MOHAN MALAVIYA’S EDUCATIONAL PHILOSOPHY - Singh, Preeti; Baldodiya, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Madan Mohan Malaviya was an Indian educationist and political leader who contributed significantly to the development of education in India during the colonial period. The present research explores Madan Mohan Malaviya’s educational philosophy and its relevance to contemporary education in India. The present research begins by examining Malaviya’s views on education as a means of promoting social and national progress. It then analyses his vision for an education system that combines the best of Indian and Western traditions. Malaviya’s emphasis on character building, moral education and the cultivation of social responsibility is also discussed. The present research explores Malaviya’s views on teacher training and the role of the teacher in society. Malaviya believed that teachers have an important role to play in shaping the character and values of their students, and that teacher education should be based on a combination of theory and practice. Finally, the present research considers the relevance of Malaviya’s educational philosophy. Although Malaviya’s ideas developed in a very different historical context, many of the principles he propounded, such as the importance of character building and the role of teachers as moral guides, remain relevant even today.